Subsequent ischemic events associated with lower extremity amputations in patients with type 2 diabetes: A population-based cohort study. Issue 1 (January 2015) - Tsai, Feng-Chou; Lan, Yu-Ching; Muo, Chih-Hsin; Yang, Ya-Fei; Sung, Fung-Chang; Chen, Ruey-Yu; Lyu, Shu-Yu; Morisky, Donald E.
Abstract Aims To explore the risk of subsequent ischemic events in type 2 diabetes mellitus (DM) patients who had lower extremity amputations (LEAs) were compared with DM patients without LEAs. Methods A population-based cohort study was conducted utilizing the data of 2011 patients with newly diagnosed DM with and without LEAs sourced from the Longitudinal Health Insurance Database 2000 (LHID 2000) of the Taiwan National Health Insurance (NHI) program between 1996 and 2008. Main outcome measures Relative risks (RRs), hazard ratios (HRs), and disease-free rates for various ischemic events. Results In contrast with the comparison group, subjects with LEAs were more likely to reside in less urbanized areas, be white collar workers, and have higher DM-related costs (p < 0.05). Subjects with LEAs also had significantly higher risks of developing ischemic diseases, except intestinal ischemia. In the multivariate Cox proportional hazards regression model analysis, the HR of end-stage renal disease (ESRD) was highest (HR = 3.91, 95% CI = 2.38–6.42), followed by embolism and thrombosis (HR = 3.47, 95% CI = 2.12–5.67), other peripheral vascular diseases (HR = 3.11, 95% CI = 2.11–4.57), atherosclerosis (HR = 2.64, 95% CI = 1.60–4.35), retinopathy (HR = 2.24, 95% CI = 1.79–2.80), cerebral ischemia (HR = 1.61, 95% CI = 1.25–2.06), and coronary artery disease (HR = 1.44, 95% CI = 1.18–1.74). Conclusions DM patients with LEAs had significantly higher risks for subsequent ischemic events, particularly among men. The greatest risk detected among DM patients with LEA's was for end-stage renal disease. Disease free survival rates also indicated that the course of generalized DM ischemia proceeded despite treatment.